DAMPAK KURIKULUM MERDEKA TERHADAP KEMANDIRIAN DAN KREATIVITAS SISWA DI SDI WOLOMARANG : Kurikulum merdeka sangat membantu kreativitas dan kemandirian siswa - Rawin, Seftiana Clara; Marsela Rinielda Dua,Mario Florentino, Sturmius Theofanus Lering (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Independent Curriculum is a new policy in the world of Indonesian education that aims to provide flexibility to educational units and educators in designing learning according to the needs of students. This study aims to examine the impact of the implementation of the Independent Curriculum on increasing student independence and creativity at SDI Wolomarang. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the Independent Curriculum has a positive influence on student independence and creativity, although there are still some challenges in its implementation. Keywords: Independent Curriculum, independence and creativity, SDI Wolomarang